Insulin resistance and coronary artery disease in non-diabetic patients: Is there any correlation? - jamshid Vafaeimanesh; Mahmoud Parham; Samieh Norouzi; Parinaz Hamednasimi; Mohammad Bagherzadeh (Babol University of Medical Sciences, 2018)
Background: Cardiovascular diseases are the most common causes of death in the world and type 2 diabetes is one of them because it is highly prevalent and doubles heart disease risk. Some studies suggest that insulin resistance is associated with coronary artery disease in non-diabetics. The aim of this study was to evaluate the association of insulin resistance (IR) and coronary artery disease (CAD) in non-diabetic patients. Methods: In this cross-sectional study, from September 2014 to July 2015, 120 patients referring to Shahid Beheshti Hospital of Qom were evaluated. Their medical history, baseline laboratory studies, BMI and GFR were recorded. After 8 hours of fasting, blood samples were taken from the patients at 8 am, including fasting glucose and insulin level. We estimated insulin resistance using the homeostatic model assessment index of IR (HOMA-IR). Finally, we evaluated the association between IR and CAD. Results: Totally, 120 patients were assigned to participate in this study, among them, 50 patients without CAD and 70 with coronary artery stenosis. Insulin resistance (HOMA-IR> 2.5) was positive in 59 (49.3%) patients and negative in 61 (50.7%) patients. Hence, the correlation between IR and CAD was not statistically significant (P=0.9). Conclusions: In this study, although the correlation was not found between insulin resistance and coronary heart disease, among men, we found a significant association between coronary heart disease and insulin resistance.